LEARNER AUTONOMY IN THE INDONESIAN EFL SETTINGS - Lengkanawati, Nenden Sri (Universitas Pendidikan Indonesia, 2017)
Learner autonomy in Indonesian educational institutions has not commonly been listed as a teaching-learning objective, and most teachers seem to be hardly acquainted with learner autonomy (LA). Therefore, it is very essential to conduct a study of LA as perceived and experienced by school teachers and to find out the importance of LA training for professional development. A questionnaire was used to collect the data about English teachers’ perceptions regarding LA and LA-based practices. In addition, an LA training was conducted to see its significance for professional development. After the data were qualitatively and quantitatively analyzed, it was found that the participating teachers tended to maintain that autonomy should be inculcated among learners, and that the LA concept should not be misinterpreted as learning without a teacher. Concerning choices and decisions by the learners, it was believed that learners’ making choices about how they learned and what activities they did, and involving them to decide what and how to learn could promote autonomy among learners. As regards LA-based teaching-learning practices, it was revealed that most teachers desired to implement LA principles in their teaching-learning contexts, although they identified that many of the LA principles were not that feasible to apply in their situation. It was also found that LA training could improve the teachers’ perceptions regarding LA concepts and principles. There were some constraints which could make learner autonomy difficult to develop among Indonesian learners in general: limited time allotted for the implementation of the curriculum, learners’ lack of autonomous learning experience, too much focus on national examinations, and insufficient proficiency of English. LA-based teaching-learning practices were most desired; however, many were considered as having insufficient feasibility. In this respect, commitment is certainly the key to success in inculcating LA principles as well as implementing them in the classroom setting.